Losy zawodowe absolwentów Uniwersytetu Jagiellońskiego na przykładzie rocznika 2007/2008 w świetle badań prowadzonych przez zespół badawczy biura karier Uniwersytetu Jagiellońskiego = Career History of Jagiellonian University Graduates Illustrated by the Example of Year 2007/2008 in the Light of Research Run by Research Team from Career Office of the Jagiellonian University - Ćwiąkalska, Maria; Hojda, Paulina; Ostrowska-Zakrzewska, Mariola (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this article is to present the most important results of the explorative research "Career History of Jagiellonian University Graduates of Year 2007/2008" realized by the Research Team created by Career Office of the Jagiellonian University. Since year 2007/2008, periodic monitoring of graduates careers has been undertaken systematically, referring in this way to traditions of West European universities , which have been conducting this type of research for years.
Keywords: Uniwersytet Jagielloński; absolwenci; losy absolwentów studiów wyższych